Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis

Surpassing the love of men: Romantic friendship and love between women from the renaissance to the present. - Faderman, Lillian (W Morrow, 1981)
A classic of its kind, this fascinating cultural history draws on everything from private correspondence to pornography to explore five hundred years of friendship and love between women.Surpassing the Love of Men throws a new light on shifting theories of female sexuality and the changing status of women over the centuries.
Keywords: amitié; amour; approches et analyses; corps; droits des femmes*; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; phallocratie; ressource en ligne; sexualité; systèmes d'oppressions; thématiques